The Neurodiversity Approach(es): What Are They and What Do They Mean for Researchers? - Dwyer, Patrick (Human development, 2022)
Abstract This paper presents the concepts of “neurodiversity” and the “neurodiversity approaches” towards disability and discusses how confusion regarding the meaning of these concepts exacerbates debate and conflict surrounding the neurodiversity approaches. For example, some claim the neurodiversity approaches focus solely on society and deny contributions of individual characteristics to disability (a controversial stance), whereas this paper joins other literature in acknowledging the contributions of both individual and society to disability. This paper also addresses other controversies related to neurodiversity, such as uncertainty regarding the scope of the approaches – to whom do they apply? – and their implications for diagnostic categories. Finally, it provides recommendations for developmental researchers who wish to carry out neurodiversity-aligned research: scholars are urged to study both individual neurodivergent people and the contexts around them; to consider both strengths and weaknesses; to recognize their own biases; and to listen to and learn from neurodivergent people.